2016
DOI: 10.1017/asr.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Masculinity and Femininity in Husbands’ Care of Wives with Cancer in Accra

Abstract: This article explores the care that husbands in Accra, Ghana, provide for wives who have been diagnosed with cancer. Making use of an inductive, qualitative approach, the study analyzes observations of and in-depth ethnographic interviews conducted with five married female cancer patients and their husbands over a ten-month period. The results suggest a strong association among husbands' care, wives' responses to husbands' care, and cultural ideals of femininity and masculinity. The findings suggest that husba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Additionally, most spouses of fathers who participated in this study from Sakora and Accra were engaged in economic activities outside the home. The women's working situation is therefore likely to play a role in men's acceptance of male performance of caregiving and housework, as many studies have shown (Atobrah and Adomako Ampofo 2016;Boni 2002;Clark 1999;Ganle 2016;Kwansa 2012). Men's acceptance of caregiving and performance of africatODAy 67(1) housework is indicative of involved fatherhood as described by G. R. Farstad and K. Stefansen (2015;see also Magaraggia 2012;McGill 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most spouses of fathers who participated in this study from Sakora and Accra were engaged in economic activities outside the home. The women's working situation is therefore likely to play a role in men's acceptance of male performance of caregiving and housework, as many studies have shown (Atobrah and Adomako Ampofo 2016;Boni 2002;Clark 1999;Ganle 2016;Kwansa 2012). Men's acceptance of caregiving and performance of africatODAy 67(1) housework is indicative of involved fatherhood as described by G. R. Farstad and K. Stefansen (2015;see also Magaraggia 2012;McGill 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women often provide personal care (such as bathing, cooking, laundry, and dressing). In contract, men provide financial care (such as giving money for food and paying medical and other types of bills) [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Women and children did all the instrumental care of cleaning, meal preparation, and all care activities in the personal domain. Conversely, men provided necessary material provisions for maintenance (Atobrah & Ampofo, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…She must be subservient, patient, and compassionate. Alternatively, hegemonic masculinity is associated with success in the economic and social spheres, characterised by the ability to provide resources, protection, defence and safety for the family, particularly female members (Atobrah, 2019; Atobrah & Ampofo, 2016). This suggests a significant imbalance in sexual life between men and women.…”
Section: Discussionmentioning
confidence: 99%